FEEDBK: a novel approach for providing feedback. (10th May 2019) - Hall, Catriona; Peleva, Emilia; Vithlani, Rohan H; Shah, Savan; Bashyam, Maria; Ramadas, Mayurun; Horsburgh, Jo; Sam, Amir H
Summary: Background: High‐quality feedback is fundamental to students' learning. We describe and evaluate FEEDBK, a novel feedback tool that encompasses the f ocus of learning, student self‐e valuation (reflection), the e ncounter with the patient (professionalism), one task that the student should continue to d o (reinforcement), one task that they could do b etter (improvement) and a k ey take‐home message for self‐directed learning. Methods: Medical students received regular bedside teaching and feedback during a 9‐week clinical placement at a teaching hospital. Teaching fellows gave feedback in their usual style during weeks 1–3 and then used the FEEDBK tool during weeks 4–9. Questionnaires and focus groups were used to evaluate the students' experience of feedback before and after the introduction of FEEDBK. Results: FEEDBK significantly enhanced the feedback experience across six domains: identifying learning objectives, chance to reflect, feedback on communication skills/professionalism, specific suggestions for improvement, clear take‐home message and personalised feedback. The analysis of the feedback from focus groups yielded four categories: (i) FEEDBK influenced the feedback process (delivering timely feedback); (ii) the nature of the feedback (enhancing both the quantity and the quality of the feedback received); (iii) the structure of the feedback; and (iv) the evolution of teaching and learning . Discussion: FEEDBK may enhance both the quantity and the quality of feedback and has the potential to improve the quality of teaching. It provides teachers with a quick and easy‐to‐follow framework to signpost curriculum‐aligned feedback.